2018
DOI: 10.1051/sicotj/2018017
|View full text |Cite
|
Sign up to set email alerts
|

Extended trochanteric osteotomy: comparison of 3 modes of fixation: metallic wires, cables, plate, about a series of 157 cases

Abstract: Introduction: The trans femoral osteotomy was initially described by Wagner in 1987 and the extended trochanteric osteotomy (ETO) was described by Younger et al. in 1995 and is considered to be the gold standard technique for removal of well-fixed femoral stems in revision total hip arthroplasty (THA). The purpose of this report is: to compare the different types of fixation metallic wires, cables, metallic reinforcement plate (MRP) we have used in revision THA where an ETO was performed;analyse the clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Abdel et al [9] evaluated the outcomes of 612 ETOs and found 50% postoperative fractures occurred at the most proximal cable of the GT due to concentrated stress and devitalized bone, which is consistent with the finding in our series, in which two fractures occurred in the cable group. In cases where the bone conditions were poor, the scratch in femoral cortex could occur and solid fixation or union by cables alone were hard to achieve [16,17]. The significant decreased ALA and migrations in cable group suggested the tightened cables could not only increase the risk of fracture but also cause inability of fragment to overcome the pull of the abductors before the union, which, to the best of our knowledge, has never been evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 80%
“…Abdel et al [9] evaluated the outcomes of 612 ETOs and found 50% postoperative fractures occurred at the most proximal cable of the GT due to concentrated stress and devitalized bone, which is consistent with the finding in our series, in which two fractures occurred in the cable group. In cases where the bone conditions were poor, the scratch in femoral cortex could occur and solid fixation or union by cables alone were hard to achieve [16,17]. The significant decreased ALA and migrations in cable group suggested the tightened cables could not only increase the risk of fracture but also cause inability of fragment to overcome the pull of the abductors before the union, which, to the best of our knowledge, has never been evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 80%
“…There are many previous studies that have examined ETO in patients who underwent complex total hip arthroplasty or total hip arthroplasty revision following periprosthetic fractures, infection, or aseptic loosening, and that have compared the results of the use of cables, and cable grip and cable plate systems used for fixation after ETO. 1 - 3 , 13 , 14 In a retrospective study by Prudhon et al, 15 ETO was performed on 157 patients due to revision total hip surgery. In the fixation of the osteotomized trochanteric fragment, wires and cables were used with tension applied manually.…”
Section: Discussionmentioning
confidence: 99%
“…As the incidence of total hip arthroplasty (THA) continues to rise, demand for revision THA is also increasing [1][2][3][4]. Instability, aseptic loosening, and periprosthetic joint infection (PJI) are the most common indications for revision hip replacement [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…facilitates component removal, cement removal, reaming, debridement, and preparation of a new implant insertion while minimizing surgical complications such as canal perforation, trochanteric fracture, and shaft fracture [3,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation